2001
DOI: 10.1128/jb.183.19.5554-5561.2001
|View full text |Cite
|
Sign up to set email alerts
|

Extragenic Suppressors of Growth Defects inmsbB Salmonella

Abstract: Lipid A, a potent endotoxin which can cause septic shock, anchors lipopolysaccharide (LPS) into the outer leaflet of the outer membrane of gram-negative bacteria. MsbB acylates (KDO) 2 -(lauroyl)-lipid IV-A with myristate during lipid A biosynthesis. Reports of knockouts of the msbB gene describe effects on virulence but describe no evidence of growth defects in Escherichia coli K-12 or Salmonella. Our data confirm the general lack of growth defects in msbB E. coli K-12. In contrast, msbB Salmonella enterica s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 30 publications
7
71
1
Order By: Relevance
“…Mutation of pagP in this msbB-deficient background aggravates the antibiotic sensitivity (Table 2), which suggests that lipid A palmitoylation can partially compensate for the absence of myristate in lipid A. Previous studies of msbB mutants have revealed increased sensitivity to antibiotics in Salmonella but not in E. coli K-12 (46,47), and our observations confirm these latter findings (Table 2). We also observed slow growth and poor growth of msbB-and msbB/pagPdeficient E. coli O157:H7, respectively, on lactose MacConkey agar plates, which contain bile salts that select against organisms with a compromised OM permeability barrier (not shown).…”
Section: Resultssupporting
confidence: 82%
“…Mutation of pagP in this msbB-deficient background aggravates the antibiotic sensitivity (Table 2), which suggests that lipid A palmitoylation can partially compensate for the absence of myristate in lipid A. Previous studies of msbB mutants have revealed increased sensitivity to antibiotics in Salmonella but not in E. coli K-12 (46,47), and our observations confirm these latter findings (Table 2). We also observed slow growth and poor growth of msbB-and msbB/pagPdeficient E. coli O157:H7, respectively, on lactose MacConkey agar plates, which contain bile salts that select against organisms with a compromised OM permeability barrier (not shown).…”
Section: Resultssupporting
confidence: 82%
“…All strains are stored frozen at −80°C in 15% glycerol. Bacterial media used were LB (Miller, 1992) which contained 1% tryptone, 0.5% yeast extract, and 1% NaCl or LB plates containing 1.5% agar, LB-0 (LB no NaCl; Murray et al, 2001), and a novel media CTY containing 0.2% casamino acids, 0.2% tryptone, 0.1% yeast, and 0.9% NaCl adjusted to pH 7.4 with 0.2 M NaOH, which we found was less toxic to mammalian cells than LB, yet supported bacterial protein expression. Antibiotics used were 100 µg/mL ampicillin (Amp 100 ) except in CTY which was 50 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The gene msbB encodes an enzyme that adds terminal myristyl groups to lipid A (Somerville et al, 1996). Without the LPS modifying enzyme, strains of Salmonella are known to possess growth defects as well as EGTA and galactose-MacConkey medium sensitivity (Murray et al, 2001). In strain S. Typhimurium 14028s, these effects are partially suppressed by the Suwwan deletion, a spontaneous recombination event causing the excision of a 108-kilobase region of the genome (Murray et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial cell cultures were routinely grown in MSB (Murray et al, 2001) medium (1% tryptone, 0.5% yeast extract, 2 mM MgSO 4 , 2 mM CaCl 2 ) at 37°C.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%